Doctor's orders ; Greening of the Philippines ; Die hard (Fans) [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Discusses the medical malpractice cases; environmental consciousness among Filipinos and the adulation of fans to their idols.
Doctor's orders (16 min.) -- Greening the Philippines (14 min.) -- Die hard (Fans) (10 min.)
VHS.
Keywords: Medical personnel -- Malpractice. -- Philippines; Conservation of natural resources -- History. -- Philippines; Environmentalism; Fans (Persons) -- Philippines